Nature of Impact of Avalanche Snow on an Obstacle - Puzanov,V. P. (1966)
The time history of the impact force of two snow avalanches has been recorded at the Kirovsk station of the snow and meteorological service of the Apatit combine using a recording instrument designed by M. I. Gol'tsman. The first recording was for dry fresh snow, while the second was for old snow with a structure in the form of large blocks. (Author) Trans. of Akademiya Nauk SSSR. Izvestiya. Seriya Geograficheskaya i Geofizicheskaya, v7 p86-88 1943.